2015
DOI: 10.1021/acs.inorgchem.5b01004
|View full text |Cite
|
Sign up to set email alerts
|

A2MnU3O11 (A = K, Rb) and Li3.2Mn1.8U6O22: Three New Alkali-Metal Manganese Uranium(VI) Oxides Related to Natrotantite

Abstract: Single crystals of three new alkali-metal manganese uranium oxides, K2MnU3O11, Rb2MnU3O11, and Li3.2Mn1.8U6O22, have been grown from molten chloride fluxes and structurally characterized by single-crystal X-ray diffraction. The first two compounds crystallize in the trigonal space group, R3̅c, in the three-dimensional (3D), natrotantite structure composed of α-U3O8-topological layers connected via MnO6 octahedra. The Li-containing compound crystallizes in the monoclinic space group, Cc, with a related 3D struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Although both the +4 and +6 oxidation states are found in nature, by far the majority of laboratory-synthesized uranium compounds found in the chemistry literature focus on U­(VI) chemistry, which is dominated by the structure directing uranyl ([OUO] 2+ ) ion. While uranyl chemistry is a rich field that continues to produce interesting new materials, exploring the synthesis of U­(IV) containing materials is of particular interest as the U­(IV) f 2 ion exhibits properties noticeably different from those found for the U­(VI) f 0 ion. In addition, there are comparatively very few reported U­(IV) containing materials, which makes this an attractive area to investigate.…”
Section: Introductionmentioning
confidence: 99%
“…Although both the +4 and +6 oxidation states are found in nature, by far the majority of laboratory-synthesized uranium compounds found in the chemistry literature focus on U­(VI) chemistry, which is dominated by the structure directing uranyl ([OUO] 2+ ) ion. While uranyl chemistry is a rich field that continues to produce interesting new materials, exploring the synthesis of U­(IV) containing materials is of particular interest as the U­(IV) f 2 ion exhibits properties noticeably different from those found for the U­(VI) f 0 ion. In addition, there are comparatively very few reported U­(IV) containing materials, which makes this an attractive area to investigate.…”
Section: Introductionmentioning
confidence: 99%
“…With a coordination number of 6, a hypothetical uranyl ion with the formula UO 6 would have an overall charge of −6, which would favor condensation of uranyl polyhedra by sharing oxygen anions, thereby reducing the overall charge by −1 for each oxygen that is shared by two uranium polyhedra (or by −1.33 if three polyhedra share the bridging oxygen). With coordination numbers of 7 and 8 hypothetical uranyl ions would have anionic charges of −8 and −10, respectively, creating an even greater driving force for condensation into 2- or 3D structures to allow sharing of oxygen anions, and indeed this observation has been extensively noted in the literature. , , …”
Section: Introductionmentioning
confidence: 88%
“…Hexavalent uranium exists nearly ubiquitously as the linear uranyl (UO 2 2+ ; [OUO] 2+ ) ion, which results in the uranyl oxide crystal chemistry being dominated by two-dimensional uranyl oxide sheet-anion structures. The formation of these layered structural motifs is favored by the relative inertness of the axial uranyl oxygens that typically do not participate in bonding, leaving only the equatorial anions to bond, resulting in the aforementioned sheet topology. Fluoride ligands do not possess the ability to form double bonds and, therefore, are unable to form uranyl bonds with uranium.…”
Section: Introductionmentioning
confidence: 99%
“…In recent works , we have shown that soft N-donors in the presence of ionic liquids (ILs) can effectively compete with O-donors and coordinate to f -elements, particularly uranyl groups, leading to all sorts of metal–organic materials from isolated complexes to 2D formations and hydrogen-bonded MOFs. Although uranyl nodes are frequently pentacoordinated, they share vertices or edges with six identical nodes, resulting in (pseudo)­hexagonal motifs . However, this variety also includes pentagonal motifs which are rather forbidden in the crystalline solids and these range from the local 5-fold nodes to extended solids with pseudopentagonal arrangements and, ultimately, approach quasi-crystalline formations …”
Section: Introductionmentioning
confidence: 99%